2016
DOI: 10.1001/jamadermatol.2015.2680
|View full text |Cite
|
Sign up to set email alerts
|

Total-Body Examination vs Lesion-Directed Skin Cancer Screening

Abstract: IMPORTANCE Skin cancer is the most frequent cancer type. It remains unknown if and how screening programs can be organized in a cost-effective manner. OBJECTIVE To compare the 2 screening strategies of systematic total-body examination (TBE) and lesion-directed screening (LDS), with a focus on the participation rate, detection rate, anxiety, and cost. DESIGN, SETTING, AND PARTICIPANTS Population-based cross-sectional screenings by a team of 6 dermatologists were organized in 2 sociodemographically similar regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 36 publications
1
55
1
1
Order By: Relevance
“…In contrast, lesion directed examinations are more time-efficient and have similar detection rates, but still require time-expensive face-to-face consultations and similar constraints as to total-body examinations apply. [9] Teledermatological assessments on the other hand, especially lesion directed store and forward procedures can be performed in a most speedy manner. In several former studies, the reliability of teledermatology based management recommendations was shown to be comparable to face-to-face consultations.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, lesion directed examinations are more time-efficient and have similar detection rates, but still require time-expensive face-to-face consultations and similar constraints as to total-body examinations apply. [9] Teledermatological assessments on the other hand, especially lesion directed store and forward procedures can be performed in a most speedy manner. In several former studies, the reliability of teledermatology based management recommendations was shown to be comparable to face-to-face consultations.…”
Section: Introductionmentioning
confidence: 99%
“…The development of a standardized dermatologic exam has been particularly important in screening for skin cancer. Skin surveillance for skin cancer has been assessed in several studies . This type of screening is usually done by physicians, but patients are also instructed to examine their skin on a regular basis, looking for abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, the annual cost of treating newly diagnosed melanoma in the United States was $457 million, and by 2030 it is expected to increase 252.4% to $1.6 billion. 9 In the study by Hoorens et al, 4 the screening cost per melanoma detected varied from €4631 to €7449. The cost of detecting a melanoma by self-detection of concerning lesions was, not surprisingly, less than by population-based screening.…”
mentioning
confidence: 99%
“…The Belgian study by Hoorens et al 4 tests 2 potential innovations for population-based organized screening for skin cancer. First, they compared a general population–based invitation for screening with a more selective approach based on concerning lesions in 2 communities with equivalent populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation